ESTUDO DE CASO COM PACIENTE COM DIAGNÓSTICO DE SÍNDROME DE GUILLAIN BARRÉ. - Morais, Cheila L. O.; Grimm, Júlia Y.; Santoni, Michele; Weiss, Elisângela d. C.; Feistel, Eliane C. d. S.; Kolankiewicz, Adriane C. B. (Salão do Conhecimento, 2013)
Resumo